Experimental repurposing of metformin for Crohn’s disease in trinitrobenzene sulfonic acid induced colitis model in BALB/c mice - Phirke, Chetan N.; Visaria, Harshal J.; Bhide, Shruti S.; Kothari, Rahul S.; Patil, Saurabh R.; Abhyankar, Neha M. (International Journal of Basic & Clinical Pharmacology, 2024)
Background: Inflammatory bowel disease (IBD) is characterized by repetitive episodes of inflammation of the gastrointestinal tract caused by an abnormal immune response to gut microflora. It includes two types: Ulcerative colitis (UC), which causes widespread colon inflammation, and Crohn’s disease (CD). The current therapy focuses on symptom relief and provides inadequate maintenance of remission and quality of life improvement. Metformin has already been repurposed in few studies with dextran sulphate sodium (DSS) induced colitis. We aimed to evaluate the effect of metformin in TNBS induced acute on chronic colitis, to mimic the relapsing-remitting nature of CD in humans, which has not been done before. Methods: Objectives were, phase I- evaluation of the effect of metformin in TNBS induced acute colitis in BALB/c mice. Phase II- evaluation of the effect of metformin in TNBS induced chronic colitis in BALB/c mice. Phase III- Evaluation of the effect of metformin in TNBS induced acute on chronic colitis in BALB/c mice. Materials And Methods: Trinitrobenzene sulfonic acid (TNBS) was used for inducing both acute, chronic and acute on chronic colitis in BALB/c mice. 36 BALB/c mice were divided into 4 groups i.e. normal control, disease control, positive control and test drug. Effect on DAI score, lower colon weight by length ratio, macroscopy and histopathology were assessed. Results: Metformin showed significant improvement (p<0.05) in all the variables assessed i.e. reduction of (Disease Activity Index) DAI score, lower colon weight by length ratio, lower colon macroscopic score and lower histopathological score in comparison to the disease control group in all the phases i.e. acute (day 5), chronic (day 22) and acute on chronic (day 25). However, the effects were comparable to the positive control. Conclusions: Metformin has potential to be repurposed for Crohn’s disease as it showed comparable efficacy in all three phases.